2002
DOI: 10.1038/sj.bjc.6600221
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4/CXCL12 expression and signalling in kidney cancer

Abstract: CXCL12 (SDF-1), a CXC-chemokine, and its specific receptor, CXCR4, have recently been shown to be involved in tumourgenesis, proliferation and angiogenesis. Therefore, we analysed CXCL12α/CXCR4 expression and function in four human kidney cancer cell lines (A-498, CAKI-1, CAKI-2, HA-7), 10 freshly harvested human tumour samples and corresponding normal kidney tissue. While none of the analysed tumour cell lines expressed CXCL12α, A-498 cells were found to express CXCR4. More importantly, real-time RT–PCR analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
172
1
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(187 citation statements)
references
References 31 publications
8
172
1
4
Order By: Relevance
“…Although the predominant function of CXCL12-CXCR4 in tumorigenesis is to induce metastases, studies have also indicated that this chemokine ligand-receptor pair is important in promoting angiogenesis (33,34). CXCL12 may be involved in up-regulating expression levels of vascular endothelial growth factor and basic fibroblast growth factor in that subcutaneous injection of CXCL12 into mice induced formation of local small blood vessels (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Although the predominant function of CXCL12-CXCR4 in tumorigenesis is to induce metastases, studies have also indicated that this chemokine ligand-receptor pair is important in promoting angiogenesis (33,34). CXCL12 may be involved in up-regulating expression levels of vascular endothelial growth factor and basic fibroblast growth factor in that subcutaneous injection of CXCL12 into mice induced formation of local small blood vessels (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…The chemokine receptor, CXCR4, and its endogenous ligand SDF-1 have been shown to be key components in both chemokineinduced leucocyte trafficking (Aiuti et al, 1997(Aiuti et al, , 1999Hamada et al, 1998) and the migration of malignant epithelial cells to the BMS (Koshiba et al, 2000;Muller et al, 2001;Robledo et al, 2001;Murakami et al, 2002;Schrader et al, 2002;Taichman et al, 2002; Sun et al, 2003). This has led to the hypothesis that CXCR4 is the key component of metastatic implantation in bone marrow and that it represents an important therapeutic target for metastatic bone disease.…”
Section: Discussionmentioning
confidence: 99%
“…These include cancers of the prostate (Taichman et al, 2002), kidney (Schrader et al, 2002), lung (Burger et al, 2003) breast (Muller et al, 2001) and skin (Robledo et al, 2001;Murakami et al, 2002). Cells from these tumour types share many of the trafficking characteristics of haematopoietic stem cells (HSC) (Muller et al, 2001).…”
mentioning
confidence: 99%
“…Metastatic cells of solid tumors hijack the chemokine signaling network leading to colonization of ectopic tissues with those carcinomas, with CXCR4 and CXCL12 receiving the most attention in regards to metastasis of colon, breast, kidney and lung carcinomas (Muller et al, 2001;Schrader et al, 2002;Phillips et al, 2003;Zeelenberg et al, 2003). This research has lead to the current model wherein CXCR4 expression on metastatic cells enables those cells to home to organs abundantly expressing CXCL12.…”
Section: Introductionmentioning
confidence: 99%